Design Of Coreless Pcb Transformer For A Fullbridge Dc-Dc Converter Application - Hashemi, Mohammadali (2013)
This thesis present acoreless Printed Circuit Board (PCB) transformer developed for a full-bridge direct current (DC) to DC converter application. During the last decade, the coreless PCB transformer was used in high frequency applications. It was found that these transformers have good features in high frequency range and not useful at frequencies smaller than 300-400 kHz.After one decade of utilizing coreless PCB transformers due to some problems such as low coupling factor, high leakage inductance and low voltage gain, the performance of these transformers reduced. The most important objectives of this thesis are modification of the design, improve performance and increase energy efficiency of both coreless PCB transformer and full-bridge DC-DC converter. Based on these objectives, a three layer coreless PCB transformer is chosen to be designed and simulated by using CST Studio 3D software. This transformer can be employed for both signal and power transfer at low power level. In this case, there are two primary and two secondary windings that they are connected in series. In addition, this research also improves a high frequency fullbridge DC to DC converter using high speed switching devices. The designed converter operates in MHz frequency region. By increasing the switching frequency, the size of bulky magnetic components and parts of the converter is reduced. The input voltage region of converter is varied from 10-30V DC with a nominal supply voltage of 30V. In order to improve energy efficiency and reduce losses, the zero voltage switching (ZVS) technique was used in this converter. The maximum energy efficiency of the designed converter is identified to be 82% at a frequency of 1 MHz and it is also shown that the efficiency is more than 75% in the voltage range of 10- 30V.